The evolution of S100B inhibitors for the treatment of malignant melanoma. (January 2013) - Hartman, Kira G; McKnight, Laura E; Liriano, Melissa A; Weber, David J
Malignant melanoma continues to be an extremely fatal cancer due to a lack of viable treatment options for patients. The calcium-binding protein S100B has long been used as a clinical biomarker, aiding in malignant melanoma staging and patient prognosis. However, the discovery of p53 as a S100B target and the consequent impact on cell apoptosis redirected research efforts towards the development of inhibitors of this S100B–p53 interaction. Several approaches, including computer-aided drug design, fluorescence polarization competition assays, NMR, x-ray crystallography and cell-based screens have been performed to identify compounds that block the S100B–p53 association, reactivate p53 transcriptional activities and induce cancer cell death. Eight promising compounds, including pentamidine, are presented in this review and the potential for future modifications is discussed. Synthesis of compound derivatives will likely exhibit increased S100B affinity and mimic important S100B–target dynamic properties that will result in high specificity.